2018
DOI: 10.1093/ejo/cjy050
|View full text |Cite
|
Sign up to set email alerts
|

Relations of laterality and chewing sidedness in twins

Abstract: Preferred chewing side generally seemed to follow the side where other lateralities occur; however, monozygotic twins seemed to be more receptive to it. True-right sided were more evenly distributed than non-right sided by the preferred chewing side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
(49 reference statements)
1
9
0
Order By: Relevance
“…Several cross‐sectional studies have reported an association between functional or postural lateral preferences and masticatory laterality . Other cross‐sectional studies have found the side with more occluding teeth, more severe occlusal wear, higher bite force and better masticatory performance to be the side more frequently chosen for chewing .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several cross‐sectional studies have reported an association between functional or postural lateral preferences and masticatory laterality . Other cross‐sectional studies have found the side with more occluding teeth, more severe occlusal wear, higher bite force and better masticatory performance to be the side more frequently chosen for chewing .…”
Section: Discussionmentioning
confidence: 99%
“…28,39,40 Several cross-sectional studies have reported an association between functional or postural lateral preferences and masticatory laterality. 10,[19][20][21][22] Other cross-sectional studies have found the side with more occluding teeth, more severe occlusal wear, higher bite force and better masticatory performance to be the side more frequently chosen for chewing. 8,18,20,[24][25][26] However, due to the crosssectional design of these studies, they were unable to demonstrate whether an increase in masticatory performance on one side would be the result or the cause of the preference of this side for chewing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gender and race also affect PCS; women have been found to chew more asymmetrically compared to men, and Caucasian children to have more right-side wear than African-American children [19,25]. Among twins, the secondborn twin has PCS on the right side more frequently than the first-born twin [26]. Young children usually chew quite asymmetrically because they are incapable of moving food from one side to the other [6].…”
Section: Introductionmentioning
confidence: 99%